Avaliação de tensões residuais e validação da resistência mecânica de juntas soldadas conforme ASME IX 2017 - Silva, Ricardo Martins (2018)
The purpose of this work was to verify quantitatively and qualitatively the influence of the residual stresses of the mechanical resistance of welded joints in accordance to ASME IX (2017). Then, it was adopted as comparative criterion, the essential variables (bevel angle of the Vee-groove and electrode wire diameter) and nonessential variables (shielding gas and preheat temperature) for the Gas Metal Arc Welding (GMAW), also known as MIG / MAG (Metal Inert Gas / Metal Active Gas). It was tried to evaluate the real influence of these variables on the generation of residual stresses and, in addition, to verify how much it affects the mechanical strength of the joints by means of destructive mechanical tests such as tension and bending tests. For such measurements, the non-destructive X-Ray Diffraction (XRD) technique was used, allied to the treatment of the surface by electrolytic polishing. In order to intensify the generation of residual stresses, it was used the inversely proportional ratio between distortions and residual stresses, restricting the movement of test plates during the welding process. As test premises, the heat input, current and deposition by constant welding length remained. The results obtained for the nonessential variables were contradictory with the expected ones, according to the literature. The increase in the bevel angle decreased the residual stresses, whereas the increase in the electrode wire diameter proved to be sufficiently influential in the generation of residual stresses. The essential variables show consistent results. The addition of the preheat temperature decreased the residual stresses, while the use of a gas with higher thermal conductivity (CO2 compared to the 75% Ar + 25% CO2 mixture) increases the residual stress values. The mechanical tests showed less dependence on the residual stresses, obtaining values for the Yield Strength and Tensile Strength, greater, for the welded joint, in relation to the base metal.